Biomechanical measures of neuromuscular control and valgus loading of the knee predict anterior cruciate ligament injury risk in female athletes - Hewett, T. E.; Myer, G. D.; Ford, K. R.; Heidt, R. S.; Colosimo, A. J.; McLean, S. G.; van den Bogert, A. J.; Paterno, M. V.; Succop, P. (The American Journal of Sports Medicine, 2005)
Background: Female athletes participating in high-risk sports suffer anterior cruciate ligament injury at a 4- to 6-fold greater rate than do male athletes.